Achievement Test: How it Can be a Reliable and Valid Tool in Educational Research? - I.P., Gowramma; Bhattacharya, Dipak (JOURNAL OF INDIAN EDUCATION, 2022)
The development of achievement test is a crucial part of experimental and developmental research in the field of education. A consistent and accurate achievement test can enumerate the certified outcome of participants. The present study deals with the construction of an achievement test in a systematic manner and logical technique for the pupils of Class VIII in geography. In the present investigation, objective type achievement test with blueprint was prepared and an enquiry was completed to find out the difficulty level and discriminative index of each item. The nature of questions for achievement test consisted of true or false or fill in the blanks and multiple choices. This study can be useful for analysts, educators and other related professionals to set up a reliable and valid achievement test. The study uncovered that the scholastic achievement test for segment instruction is consistent and appropriate.